Mind Mapping Technique in Developing Students’ Speaking Skill - Wahyudi Wahyudi; Rika Irawati (Jurusan Akuntansi Politeknik Negeri Pontianak, 2019)
The purpose of this research is to investigate how significant the students’ speaking development through Mind Mapping Technique is. This study was conducted to 36 students of the first semester of Public Sector Accounting of Politeknik Negeri Pontianak in academic year of 2017/2018. The pre-experimental research was used for the purpose of this study; therefore, both pre test and post test were conducted for data collection. The finding of this study shows that there is significant development on students’ speaking skill through Mind Mapping Technique.